The influence of Melaka traditional house in Muar / Nor Akmar Busero - Nor Akmar Busero (Faculty of Architecture, Planning and Surveying, 2013)
Learning the history of an area is not easy. Man must ieam and study with the right methods in order to produce the correct facts containing a solid substance that can be accepted by all parties. Everything that exists on earth is sure to have their own history to our exploration such as the existence of an area, the presence of people in a particular area or shelter design that they live up to the emergence of a tradition that should be passed to generations. Malay tradition that has been practiced since long ago involves a lot of things which is a traditional nature of a heritage or way of life practiced from generation to generation such as traditional clothing, traditional medicine, traditional games and traditional house. The traditional house is an aesthetic value which is very valuable to our country and is rarely found today. Melaka is a state which rich with traditional houses known as Traditional Malay House of Melaka. However, Muar, bordering the states have some characteristics of Traditional Malay house associated with the design house of Melaka. So, this research is to study the influence of Melaka Traditional House in Muar. The influence of Melaka Traditional House in Muar is not something new in our life today. Muar, although has lack of history and archaeological evidence, but still this place has its own record of the relationship between Melaka and Muar by some of the influence from Melaka that is existing in Muar District mostly at border between Muar and Melaka and nearby place such as Kesang, Merlimau, Sungai Rambai, Bukit Kangkar and Tangkak. In this chapter, the study is to investigate the significant of this study and to recognize why actually Melaka Traditional House had influence Muar houses. The study is focus on the objective and problems statement that appear to achieve the aim of this study. Moreover, this chapter also discuss on the significant of this research and show how the flow of the data collection in the methodology process.